2021
DOI: 10.1107/s2059798320016071
|View full text |Cite
|
Sign up to set email alerts
|

C-phycocyanin as a highly attractive model system in protein crystallography: unique crystallization properties and packing-diversity screening

Abstract: The unique crystallization properties of the antenna protein C-phycocyanin (C-PC) from the thermophilic cyanobacterium Thermosynechococcus elongatus are reported and discussed. C-PC crystallizes in hundreds of significantly different conditions within a broad pH range and in the presence of a wide variety of precipitants and additives. Remarkably, the crystal dimensions vary from a few micrometres, as used in serial crystallography, to several hundred micrometres, with a very diverse crystal morphology. More t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…In a comparison with the crystal model of Spirulina platensis CPC ( Sp CPC; PDB ID: 1GH0), the crystals of which contained two hexamers in the asymmetric unit 17 , the root mean square deviation (rmsd) value was 0.68 Å over 1,993 Cα atoms, supporting the formation of a well-established hexameric (αβ) 6 state. The α and β subunits of Tl CPC-6 shared 68–86% and 65–87% sequence identities, respectively, with the previously reported crystal models of CPCs 14 27 . The X-ray crystallographic analysis of Tl CPC-6 showed that phycocyanobilins (PCBs), i.e., the chromophores in CPCs, were covalently bonded at the conserved Cys residues of αCys84 (α84PCB), βCys82 (β82PCB), and βCys153 (β153PCB) (Supplementary Fig.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In a comparison with the crystal model of Spirulina platensis CPC ( Sp CPC; PDB ID: 1GH0), the crystals of which contained two hexamers in the asymmetric unit 17 , the root mean square deviation (rmsd) value was 0.68 Å over 1,993 Cα atoms, supporting the formation of a well-established hexameric (αβ) 6 state. The α and β subunits of Tl CPC-6 shared 68–86% and 65–87% sequence identities, respectively, with the previously reported crystal models of CPCs 14 27 . The X-ray crystallographic analysis of Tl CPC-6 showed that phycocyanobilins (PCBs), i.e., the chromophores in CPCs, were covalently bonded at the conserved Cys residues of αCys84 (α84PCB), βCys82 (β82PCB), and βCys153 (β153PCB) (Supplementary Fig.…”
Section: Resultssupporting
confidence: 69%
“…173), and most showed orientationally aligned hexameric CPCs in crystals. Only two previous reports indicated that CPCs were crystallized in the orthorhombic space group, with these crystals containing two types of orientation 27 , 30 . Although Tl CPC-6 was also crystallized in the primitive orthorhombic space group ( P 2 1 2 1 2), hexameric CPCs were orientationally aligned in the crystal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, crystal structure determination reveals the additives as bound and ordered ligands and enables researchers to understand how the additives help to form or stabilize a crystal structure (De Yoreo & Vekilov, 2003). For example, the crystal structure of C-phycocyanin was mediated by tetracaine from the MORPHEUS III mix 'anaesthetic alkaloids' (PDB code 6yqg, resolution 1.45 A ˚; Sarrou et al, 2021). However, this is not a very common scenario, and in many instances the positive impact of additives cannot be explained.…”
Section: Morpheus Additive Mixes Integrated Into Fusionmentioning
confidence: 99%
“…Subsequent accurate X-ray structural studies of C-PC from a variety of organisms were reported. In general, almost all these studies have shown that the overall sequences of the C-PC complexes are very similar, albeit slight differences in their biophysical and biochemical properties [28][29][30][32][33][34][35][36][37][38][39][40][41][42][43][44][45]].…”
Section: Introductionmentioning
confidence: 99%